Flooding in Ermita: A Comparative Case Study of Before and After the Construction of the Dolomite Beach - Jan Jylyn Galvez; Andrea T. Martin; Clark Cedrick B. Sicat; John Cris V. Wenceslao; Dennis L. Estacio (Future Science / FSH-PH Publications, 2026)
Low-lying coastal neighborhoods of Metro Manila, including Ermita, continue to struggle with flooding. Recent discussions have suggested that the 2020 Manila Bay Dolomite Beach coastal replenishment project may have made the issue worse by changing local hydrodynamics. This study used a descriptive-comparative case study design based on secondary data from peer-reviewed journal articles, government reports, academic writings, environmental assessments, and verified news articles to compare the frequency and duration of flooding in Ermita before (2015-2020) and after (2021-2025) the project's construction. High tides, severe rainfall, and inadequate drainage maintenance were the main causes of the frequent but mostly transient pre-construction floods. On the other hand, post-construction data showed more frequent and rerouted major drainage outfalls in Faura, Remedios, and Estero de San Antonio Abad as a result of artificial beach structures that reduced the effectiveness of stormwater discharge into Manila Bay. The results showed that although flooding existed before the project, the development of Dolomite Beach inadvertently decreased the urban drainage system's capacity, which prolonged Ermita's floods. In order to guarantee that environmental and aesthetic projects improve rather than jeopardize long-term resilience and public safety, the study emphasizes the vital need for thorough, multidisciplinary planning that integrates coastal engineering interventions with the current urban hydrological infrastructure.